Passing the baton : black women track stars and American identity - Ariail, Cat M., 1987- (Sport and society., 2020)
"After World War II, the United States used international sport to promote democratic values and its image of an ideal citizen. But African American women excelling in track and field upset such notions. Cat M. Ariail examines how athletes such as Alice Coachman, Mae Faggs, and Wilma Rudolph forced American sport cultures-both white and Black-to reckon with the athleticism of African American women. Marginalized still further in a low-profile sport, young Black women nonetheless bypassed barriers to represent their country. Their athletic success soon threatened postwar America's dominant ideas about race, gender, sexuality, and national identity. As Ariail shows, the wider culture defused these radical challenges by locking the athletes within roles that stressed conservative forms of femininity, blackness, and citizenship"--